Microwave and Induction Heating-Assisted Biosynthesis of 12CaO 7Al2O3 Electride from Aloe Vera Leaf Extract - Waramon LANGLAR; Areeya AEIMBHU; Pichet LIMSUWAN; Chesta RUTTANAPUN (My University, 2021)
The white powders used as precursor powders for the synthesis of 12CaO×7Al2O3 electride (C12A7:e-) were prepared by biosynthesis method using Aloe vera extract and microwave assisted synthesis. The C12A7:e- crystals were synthesized by induction heating process under a reducing atmosphere at different times of 3, 4 and 5 min. The structure of C12A7:e- powders was characterized by X-ray diffraction. The XRD analysis revealed that pure C12A7:e- powders were obtained from white precursor powders with an induction heating process time of 5 min. To confirm that the white precursor powders were transformed into C12A7:e- after induction heating process for 3, 4 and 5 min, the optical absorption spectra of powders were investigated by an UV-Vis diffuse reflectance spectrometer in the wavelength range of 200 – 800 nm. The results show the optical absorption bands at 2.8 eV for the white precursor powders with induction heating time of 3, 4 and 5 min. This is due to the C12A7 was transformed into electride (C12A7:e-). Therefore, the results on the optical absorption spectra are in good agreement with the XRD results.
Keywords: Induction Heating; Aloe Vera; Ammonia Synthesis and Nitrogen Reduction